Species of the subgenera Aquilaspio and Prionospio (Polychaeta: Spionidae: Prionospio) from the southern coast of Turkey (Levantine Sea, eastern Mediterranean), with description of a new species and two new reports for the Mediterranean fauna - Dagli, Ertan; Çinar, Melih Ertan (Zootaxa, 2009)
The present study deals with species of the subgenera Prionospio (Aquilaspio) and Prionospio (Prionospio) collected from various habitats and depths along the southern coast of Turkey in September and October 2005. The examination of a large collection of material revealed 10 species, of which one species, Prionospio (P.) ergeni n. sp., is new to science; two species, P. (P.) depauperata and P. (A.) krusadensis, are new to the Mediterranean fauna; and one species, P. (A.) sexoculata, is new to the Turkish marine fauna. Prionospio (P.) ergeni n. sp. differs from all other Prionospio species in having three pairs of pinnate branchiae between chaetigers 2 and 4 and one pair of apinnate branchiae on chaetiger 5. Four species―P. (P.) saccifera, P. (A.) sexoculata, P. (P.) depauperata, and P. (A.) krusadensis―are aliens. The former two species could have been introduced to the Mediterranean from the Red Sea through the Suez Canal (Lessepsian migrants) and the others from the Pacific or Indian Oceans via ballast water of ships. The morphological, ecological, and distributional features of these species are discussed.